Mixed method integrative review exploring nurses' recognition and response to unsafe practice. (20th November 2015) - Blair, Wendy; Kable, Ashley; Courtney‐Pratt, Helen; Doran, Evan
Abstract: Aim: To determine how nurses recognize and respond to unsafe practice. Background: Practice guidelines and standards outline safe practice. Nurses face challenges in recognizing and responding unsafe practice. Design: Whittemore and Knafl's revised framework for integrative reviews guided the analysis. Data sources: A comprehensive search of literature exploring the identification and response to unsafe practice, was undertaken in CINAHL, Medline, Embase and PsychoINFO databases for the period 2004–2014. Review methods: Nineteen articles from 15 studies were included in the review. A mixed method integrative approach was used to review data and draw conclusions. Results: Behaviours and cues that indicate unsafe practice are influenced by organizational and individual characteristics. Individual nurses responses are variable and there are professional and personal costs associated with being reported or reporting unsafe practice. Conclusion: The small number of studies reviewed limits the conclusions that can be drawn from the review but suggest that nurses can identify unsafe practice in their peers. Individual nurses' recognition and response to unsafe practice in their peers contributes to patient outcomes and safety. Nurses need awareness training and strategies to respond to unsafe practice and reporting systems that protect reporters from repercussions. Further research investigating organizational factors and individual factors that contribute to a shift in practice across safety boundaries is required.